2020
DOI: 10.13170/depik.9.3.12623
|View full text |Cite
|
Sign up to set email alerts
|

Pola pertumbuhan dan faktor kondisi ikan sembilang (Potosus canius) di Teluk Bintan Kepulauan Riau

Abstract: One of the economically important fish included in the Plotosidae family is the Sembilang Fish. This study aims to determine the growth patterns and condition factors of the Sembilang fish. The research was conducted in July 2018. The locations of the Sembilang Fish sampling station include Dompak Island Bay, Bugis Village Bay, Madong Bay, Pengujan Bay and Tanjung Uban. The total sample of Sembilang Fish that has been obtained is 150, consisting of 80 males and 70 females. Total length ranges from 19.7-66 cm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
(3 reference statements)
1
3
0
2
Order By: Relevance
“…In this study, the analyses of the length-weight relationship of P. canius showed a negative allometric growth. This is similar to the previous studies by Yulianto et al (2020), which reported that the length-weight relationship of P. canius in Bintan Bay, Riau Islands showed a negative allometric pattern, where males fish gained W = 0.00542L 2.3347 with b = 2.3347 and females W = 0.0268L 2.5378 with b = 2.5378. Moreover, Verawati et al (2019) and Nurhayati et al (2016) also mentioned a negative allometric growth of P. canius caught in Tanjung Pinang, Riau Islands, and Musi river estuary, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the analyses of the length-weight relationship of P. canius showed a negative allometric growth. This is similar to the previous studies by Yulianto et al (2020), which reported that the length-weight relationship of P. canius in Bintan Bay, Riau Islands showed a negative allometric pattern, where males fish gained W = 0.00542L 2.3347 with b = 2.3347 and females W = 0.0268L 2.5378 with b = 2.5378. Moreover, Verawati et al (2019) and Nurhayati et al (2016) also mentioned a negative allometric growth of P. canius caught in Tanjung Pinang, Riau Islands, and Musi river estuary, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Sementara restocking merupakan salah satu upaya penambahan stok ikan tangkapan untuk ditebarkan ke perairan, pada perairan yang dianggap telah mengalami krisis akibat padat tangkap atau tingkat pemanfaatannya berlebihan (Bell et al, 2008;Kartamihardja, 2015;Jia-Qiao et al, 2021;Asriyana, 2022). Studi-studi yang sudah pernah dilakukan masih terbatas antara lain: by-catch perikanan lele laut (Asriyana et al, 2020a;Asriyana & Halili, 2021c), reproduksi dan morfometri (Dewanti, 2012;Yulianto, 2020;Asriyana dan Halili, 2021b), pertumbuhan (Jumiati et al, 2018Asriyana et al, 2020b), aspek biologis (Asriyana dan Halili, 2021b), kebiasaan makan (Syam et al, 2018;Makri et al, 2021), habitat yang disukai oleh lele laut (Asriyana et al, 2022), dan domestikasi (Asriyana et al, 2021). Namun informasi yang terkait dengan pertumbuhan maupun kelangsungan hidup pada ukuran berbeda dalam kondisi terkontrol belum terungkap.…”
Section: Pendahuluanunclassified
“…Beberapa penelitian terhadap ikan sembilang telah dilakukan di beberapa wilayah, antara lain penelitian di Konawe Selatan (Jumiati et al 2018), Sumatera Selatan (Makri et al 2021), Riau (Gurning et al 2019), Semarang-Jawa Tengah (Dewanti et al 2012), Sumatera Selatan (Fatah dan Asyari 2011), Kalimantan Tengah (Harteman 2015), Kepulauan Riau (Yulianto et al 2020;Putra et al 2020;Safitri et al 2021), dan Sumatera Utara (Astiwi 2021), Teluk Patani, Thailand (Amornsakun et al 2018), Teluk Kolono (Asriyana dan Halili 2021). Beberapa penelitian terkait ekosistem perairan, biologi ikan dan kondisi perikanan di wilayah Majakerta juga telah dilakukan, antara lain kondisi lingkungan perairan (termasuk plankton) (Widyarini et al 2017), reproduksi ikan janjan merah (Sari et al 2017), pengembangan perikanan (Maarif et al 2016), pola usaha perikanan (Nugroho dan Sulistiono 2017).…”
Section: Pendahuluanunclassified